After the collapse of communism comparative lessons of transition - McFaul, Michael 1963-; Stoner, Kathryn 1965- (Cambridge University Press, 2004)
This collection of essays is the result of a conference convened at Princeton University marking the ten-year anniversary of the collapse of the Soviet Union. Some of the best minds in post-Soviet studies focused on the task of identifying in what ways the post-Communist experience with transition has confirmed or confounded conventional theories of political and economic development. The result is a rich array of essays examining vital aspects of the transitional decade following the Soviet collapse and the comparative lessons learned. These essays explicitly tally the gains and losses to post-Soviet countries of the last ten years as well as comparing the post-Soviet experience implicitly and explicitly with that of other developing countries. Each essay blends political science theory with fresh empirical analysis